Insights into spring dust aerosol trends over North China from CMIP6 historical simulations and multi-source observations - Tong Sha; Haoxuan Li; Jingda Liu; Guiqian Tang; Yuesi Wang (Atmospheric Research, 2026)

Honokiol Ameliorates Pyroptosis in Bovine Mammary Epithelial Cells via SIRT3-Mediated Inhibition of the NLRP3 Inflammasome - Sha Tang; Yanqiong Wen; Renxin Wu; Xing Shi; Dan Li; Siqing Mao; Xiao Yang; Hang Yu; Lei Tian; Le Zhang; Lei Liu (Tissue and Cell, 2026)

Corrigendum to “Highly structured solvents enable integrated organogel networks with robust adhesion and mechanics” [Chemical Engineering Journal Volume 538, 15 June 2026, 176931] - Dongyong Sha; Yang Zhao; Ding Ding; Shuaimin Tang; Jianxing Zhang; Xiaofeng Ling; Changsheng Liu; Liang Gao; Yuan Yuan (Chemical Engineering Journal, 2026)

Distance-decay relationship reveals both horizontal and vertical dispersal limitation and source–sink relationships of phytoplankton in a deep channel-type reservoir - Xiaofeng Tang; Jian Gao; Chengying Zhang; Junyi Wu; Yaxian Wang; Sha Xu; En Hu; Sisi Ye; Chao Chang; Ming Li (ENGINEERING Environment, 2026)

Emodin alleviates radiation-induced pulmonary fibrosis by targeting cellular senescence via the mtDNA-cGAS-STING axis - Wei Duan; Yanling Sha; Xi Tang; Riu Liu; Bin Su; Meijing Huang; Xin Xun; Yunfei Ye (Biogerontology, 2026)

Integrative multi-omics identifies CYP1B1 as a candidate molecular link between toxicant exposure and ferroptosis-related epithelial stress in COPD - Lingfeng Liu; Mingjun Jiang; Muzi Lei; Kun Du; Xiangyang Ye; Dafei Wei; Xiaowu Tan; Zhuang Mi; Yao Tang; Ruiting Sun; Sha Liu (Inflammation Research, 2026)

A new sesterterpenoid with β -glucuronidase inhibitory activity from the Cordyceps -colonising fungus Aspergillus versicolour ZJUTE2 - Youmin Ying; Yixian Qiu; Jing Tang; Yuhao Lin; Sha Xu; Jiayue Ni; Yun Zhang; Cuiping Tong; Wei Mao (Natural Product Research, 2026)

The influence of infant temperament and family rearing environment on feeding practices in low-birth-weight infants discharged from the NICU during 6-12 months of age: A longitudinal study - Yunling Li; Shanshan Wang; Nanping Shen; Sha Sha; Xiaoli Tang; Ying Zhang (Appetite, 2026)

Spatial and temporal dynamics of the complexity, stability and community assembly of phytoplankton community in a deep channel-type reservoir - Xiaofeng Tang; Chengying Zhang; Sha Xu; En Hu; Chao Chang; Yuhan Ma; Daoping Xi; Ming Li (Journal of Environmental Sciences, 2026)

Highly structured solvents enable integrated organogel networks with robust adhesion and mechanics - Dongyong Sha; Yang Zhao; Ding Ding; Shuaimin Tang; Jianxing Zhang; Xiaofeng Ling; Changsheng Liu; Liang Gao; Yuan Yuan (Chemical Engineering Journal, 2026)

Resilience and Adaptability Analysis of Port-Centric Transport Networks for Meteorological Disasters: A Case of Shanghai Port - Tianni Wang; Tina Ziting Xu; Zongjie Ding; Mei Sha; Lingzhi Ye; Junqing Tang; Mark Ching-Pong Poo; Yui-yip Lau; Chengpeng Wan (Journal of Marine Science and Engineering, 2026)
Climate change has intensified the frequency and severity of meteorological disasters, posing significant challenges to the resilience and adaptability of port-centric transport networks (PCTNs) and global trade stability. Unlike previous studies that adopt generalised resilience frameworks or treat disaster types uniformly, this study develops a disaster-specific, integrated assessment framework whose novelty lies in coupling three complementary methods, each playing a distinct role: (i) integer programming optimises post-disaster recovery decisions under budgetary constraints by selecting cost-effective measures that maximise re-stored container-handling capacity; (ii) Monte Carlo simulation (10,000 iterations) captures the stochastic nature of meteorological disruptions and quantifies probabilistic resilience under typhoons, storm surges, and heavy fog; and (iii) an Analytic Hierarchy Process–Evidence Reasoning (AHP–ER) hybrid integrates subjective expert judgement with objective field data to evaluate adaptability across a four-level indicator system, thereby reducing the subjectivity of conventional multi-criteria approaches. Applied to Shanghai Port, the framework yields normalised resilience scores on a [0, 1] scale, where 1.0 denotes full operational continuity (network throughput equals demand) and values below 0.80 indicate substantial disruption requiring urgent intervention. Heavy fog produces the lowest score (0.73, ‘moderate-to-severe disruption’), followed by typhoons (0.81, ‘mild disruption’) and storm surges (0.89, ‘near-normal operation’), revealing that low-visibility events—not high-energy storms—pose the dominant operational threat at Shanghai Port. Translating these findings into practice, the study recommends the following: (1) deploying real-time visibility-monitoring (LiDAR) and AI-driven traffic-scheduling systems to mitigate fog-related disruptions; (2) reinforcing gantry-crane anchoring and prepositioning emergency power supplies in typhoon-prone berths; (3) prioritising hinterland-port handling redundancy in Jiangsu and Anhui sub-networks (adaptability scores 0.639 and 0.642); and (4) piloting an integrated Shanghai–Zhejiang cross-regional emergency-response corridor with shared berthing rights and standardised joint drills. These targeted, quantitatively grounded recommendations offer port authorities and policymakers an evidence base for prioritising infrastructure investment and organisational reform to safeguard global supply chains against escalating climatic threats.

Adaptive VP1 sites 93 and 97 modulate antigenic evolution and receptor binding of Senecavirus A: Phylogenetic analysis and validation with recombinant viruses - Jing Yang; Zhiliang Zhang; Weijia Sha; Mingyue Peng; Yize Li; Xiaoyu Ge; Jiaxuan Li; Wen Cui; Yanping Jiang; Xiaona Wang; Lijie Tang (Veterinary Microbiology, 2026)

Engineering Escherichia coli cell Factories for continuous 5′-cytidine monophosphate production via biofilm-anchored dual-enzyme cascade catalysis - Wenjun Sun; Shiya Zhu; Qiwei Dong; Shuyan Tang; Qingguo Liu; Yu Sha; Tianpeng Chen; Rui Wang; Yong Chen; Hanjie Ying (Bioresource Technology, 2026)

Effects of microplastic contamination on soil nitrogen and its bioavailability in soybean-maize rotation system - Xinkai Jia; Haoqing Li; Darrell W.S. Tang; Sha Xue; Enke Liu; Xiaomei Yang (Soil and Tillage Research, 2026)

Genome-wide identification of the laccase gene family in wheat (Triticum aestivum L.) during Fusarium pseudograminearum infection - Li-Yu Chen; Yi Diao; Ju-Hong Ma; Xiang-Xue Zhang; Rui Li; Yan Liu; Hong-Tao Tang; Zhi Wang; Sha Gao; Rui-Huan Xu; Zhen-sheng Kang; De-Jun Han; et al. (Plant Science, 2026)

The transcription factor OsERF74 positively regulates drought resistance by modulating abscisic acid catabolism in rice - Ziyi Luo; Chen Tang; Liping Wang; Xiaoyu Sha; Yuhan Zhang; Wenjiang Liu; Jingye Fu; Qiang Wang (Journal of Plant Physiology, 2026)

Diverse floral arrangement morphs of Spiranthes sinensis (Orchidaceae) enhance pollinator visitation and reproductive success when competing with syntopic co-flowering plants - Yun Wu; Lingzhi Liu; Jiali Tang; Xin Wu; Sha Shuang; Guangli Liu (Flora, 2026)

Study on the dynamic interaction between buried bent pipes and soil under the influence of oblique incidence of SV waves - Chang-lu Xu; De-long Huang; Hui-yue Wang; Sha-sha Yu; Huan-qing Song; Hang Cen; Zi-yuan Huang; Qiang Liu; Ai-ping Tang (Soil Dynamics and Earthquake Engineering, 2026)

Adaptation of microbial gene polymorphisms of the partial nitritation-anammox process for maintaining denitrification performance and robustness under salinity stress - Risen Yang; Yanxiao Wei; Jianhong Jiang; Xinying Kong; Sha Wu; Qingchang Tang; Yangkai Liu; Le Luo; E.A.E. Ali; Hong Chen (Journal of Environmental Sciences, 2026)

W-induced reconstruction of NiFe (oxy)hydroxides with abundant O-vacancies as efficient electrocatalysts for water oxidation - Zhiqun Bai; Huifang Chen; Weihao Sha; Junru Lin; Jinyuan Miao; Ao Xie; Junqing Pan; Ran Pang; Kai Yan; Pingyu Wan; Yang Tang (Fuel, 2026)

Transplantation of Skin-Derived Precursor Schwann Cells Ameliorates Secondary Brain Injury after ICH in Mice by Activating the PI3K/AKT/FOXO3a Signaling Pathway - Yuqian Tang; Yan Song; Qiuwen Sun; Muyuan Tong; Yejing Zhang; Yan Chen; Junyi Sha; Chengbin Xue; Jiabing Shen; Aihong Li (Translational Stroke Research, 2026)

Estrogen inhibits granulosa cell apoptosis via nuclear receptors by suppressing death receptor and mitochondrial pathways in goat small antral follicles - Sihai Lu; Baijuan Yue; Yaju Tang; Haoyu Xu; Rui Xu; Xiaoe Zhao; Qiang Wei; Jia Xue; Meng-Hao Pan; Sha Peng; Baohua Ma (Theriogenology, 2026)

Piezocatalysis-enhanced tribocatalytic CO2 reduction via tungsten bronze K2NdNb5O15 nanopowders - Sha Wu; Zhihong Zhu; Xinhao Song; Zuheng Jin; Liupan Tang; Chuan Jiang; Changzheng Hu; Laijun Liu; Liang Fang; Zhenxiang Cheng (Fuel, 2026)

Measurement and spatio-temporal evolution analysis of high-quality development level in China's marine economy - SHA Xiujuan; WANG Yuting; TANG Huimin (Regional Studies in Marine Science, 2025)

Chronic dietary exposure to BDE-47 can induce inflammatory responses in the brain of common carp (Cyprinus carpio) and further trigger neurotoxicity through the 5-HT pathway - Huimin Sun; Youlian Liu; Yujie Huang; Mengbin Yuan; Zujun Ye; Rong Yang; Fuqiang Sha; Ni Tang; Bo Zhou; Defang Chen; Zhiqiong Li; Xin Zhang (Science of The Total Environment, 2025)

Non-iridescent modulation of chiral structure of cellulose nanocrystals under molecular constraints - Chengliang Duan; Feiyu Tang; Jian Chen; Bin Wang; Daliang Guo; Lizheng Sha (Carbohydrate Polymers, 2025)

Highly efficient removal of radioactive iodine from solution using in situ prepared Cu0@ACF adsorbent - Liang Jiang; Xiaojiang Chen; Jun Liao; Lielin Wang; Yuxin Zhang; Sha Yang; Qiuyi Wang; Yaoyao Tang; Congcong Ding (Science of The Total Environment, 2025)

Intestinal metabolomic profiling provides insights into the molecular mechanisms for hyperuricemia-induced intestinal barrier dysfunctions in a hyperuricemia mouse model - Hailong Li; Qingli Zhang; Tingting Tang; Lei Zhu; Qu Chen; Haili Zhang; Yan Zhang; Zichu Zhao; Di Xiao; Xinlei Sha; Jingrong Mu; Jingjing Kong (Food and Chemical Toxicology, 2025)

Mechanical Behavior of Sliding Zone Soil under Compression Considering Periodic Saturation-Drying: Example from a Giant Reservoir Landslide - Sha Lu; Huiming Tang; Liangqing Wang; Xuexue Su; Bing Lyu (Journal of Earth Science, 2025)

Development of a Model Material Suitable for Reservoir Landslide Model Tests - Minghao Miao; Huiming Tang; Sha Lu; Changdong Li; Kun Fang; Yixiao Gu; Chunyan Tang (Journal of Earth Science, 2025)

Protective effects of rosmarinic acid against oxidative damage and atherosclerosis via the PI3K/AKT pathway - Tiantian Tang; Mingze Sun; Baiyuan Sha; Rui Liu; Zhiyang Ren; Liwei Li; Ye Zhang; Hao Wang; Kai Yu (Food and Chemical Toxicology, 2025)

Oak pollen infrageneric classification-based winter temperature reconstruction since the marine isotope stage 5 in Southeast China - Yinning Tang; Lu Dai; Fei Gong; Junjie Yu; Jilong Wang; Weijian Zeng; Limi Mao; Zhongjing Cheng; Longbin Sha (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Soil C-N and microbial community were altered by polybutylene adipate terephthalate microplastics - Yao Yu; Yan Wang; Darrell W.S. Tang; Sha Xue; Mengjuan Liu; Violette Geissen; Xiaomei Yang (Journal of Hazardous Materials, 2025)

Continuous manufacturing of solvent-driven poly(vinyl alcohol)-based flexible electrodes with vias conductive gels for sensitive skin-integrated electronics - Dongyong Sha; Ding Ding; Shuaimin Tang; Jianxing Zhang; Xuan Tang; Changsheng Liu; Xiaofeng Ling; Lili Sun; Yuan Yuan (Chemical Engineering Journal, 2025)

Ultrasensitive electrochemical sensor based on Cr-doped Co3O4@NiO hybrid for precise simultaneous detection of trace multiple heavy metal ions - Junping Ma; Yu Wei; Sha Yu; Jieli Tang; Shaohua Wen; Shuangli Chen; Yuanzhen Zhou (Journal of Environmental Chemical Engineering, 2025)

Integrating Bulk RNA and Single-Cell Sequencing Data Unveils Efferocytosis Patterns and ceRNA Network in Ischemic Stroke - Jing Yuan; Yu-sha Liao; Tie-chun Zhang; Yu-qi Tang; Pei Yu; Ya-ning Liu; Ding-jun Cai; Shu-guang Yu; Ling Zhao (Translational Stroke Research, 2025)

Research on the measurement and spatio-temporal evolution of marine new-quality productivity in China - Xiujuan Sha; Huimin Tang; Yuting Wang (Frontiers in Marine Science, 2025)
With the deepening development of the new round of technological revolution, marine new quality productive forces (MNQPF), as a key driver for promoting the high-quality development of China's marine economy, exhibit significant regional disparities in coastal areas. These disparities hold critical implications for formulating scientifically grounded regional development strategies. Based on the three constituent elements of Marxist productive forces, this study employs the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) entropy method, Gini coefficient, and kernel density estimation to analyze the spatial-temporal evolution of MNQPF levels across China's coastal provinces using panel data from 2012 to 2021. The findings reveal:(1) China's MNQPF has shown an upward trend, yet its overall level remains relatively low;(2) Regional imbalances persist, with the Eastern Marine Economic Circle outperforming the Southern and Northern counterparts. Regional disparities primarily stem from inter-regional differences and super-variable density;(3) Spatial heterogeneity characterizes MNQPF development, manifesting as "balanced growth in central regions vs. uneven development in northern and southern areas." In this regard, relevant discussion recommendations are put forward: (1) The Eastern Marine Economic Circle should leverage technological spillover effects to extend high-end marine industries northward to the Bohai Rim Economic Circle and southward to the Beibu Gulf Economic Zone;(2) The Northern Marine Economic Circle should advance green transformation of "marine + heavy industry" through port-economic belt construction under integrated land-sea development strategies;(3) The Southern Marine Economic Circle ought to enhance cross-border marine cooperation by capitalizing on its role as a "Belt and Road" hub, while strengthening Guangdong's radiating influence on neighboring provinces.

Enhancing single-stage partial nitritation-anammox process with airlift inner-circulation and oxygen partition: A novel strategy for treating high-strength ammonium wastewater - Runchu Wei; Zhigang Tang; Sha Wu; Risen Yang; Hanbo Yu; Jing Chen; Jingyi Jiang; Jianhong Jiang; Zhe Kong; Yanxiao Wei; Ali E.A. Elsayed; Hong Chen (Environmental Research, 2025)

Association of thallium exposure in early life with gut microbiota in neonates - Kunyan Zhao; Fei Yang; Mingyang Wu; Xiongfeng Pan; Shiting Xiang; Yan Tang; Fengmei Song; Yunlong Peng; Sha Wu; Yunhui Cao; Caixia Liu; Jun Qiu (Environmental Pollution, 2025)

Cavity as radio telescope for galactic dark photon - Yanjie Zeng; Yuxin Liu; Chunlong Li; Yuxiang Liu; Bo Wang; Zhenxing Tang; Yuting Yang; Liwen Feng; Peng Sha; Zhenghui Mi; Weimin Pan; Tianzong Zhang; et al. (Science Bulletin, 2025)

In situ activatable Disulfiram-Rhodium(III) nanocomplex for Cu chelation and STAT3 inhibition to Potentiate photodynamic and immunotherapy - Yuxia Tang; Meng Dang; Yang Li; Xuan Sha; Ziqing Xu; Jie Zhang; Feiyun Wu; Shouju Wang (Chemical Engineering Journal, 2025)

The geometry evolution of Early Paleozoic carbonate platform in the southwestern Tarim Basin, China: evidence from sequence stratigraphic analysis and seismic forward modeling - Jie Li; Zicheng Cao; Feng Geng; Suju Yang; Xuguang Sha; Mingjie Lan; Shenghou Wang; Yongchao Lu; Yangbo Lu; Daqing Tang; Zhao Zhang; Fang Hao (Frontiers in Marine Science, 2025)
Deciphering the evolution of spatial geometry of carbonate platforms in deeply buried successions is still a challenge due to the low resolution of seismic data and the constraints of drilling wells. In this study, by combining a seismic forward model, we systematically delineated the external morphology and internal architecture of seismic reflection and established a depositional model of a carbonate platform. The Lower Paleozoic strata display the high-amplitude reflection in the Lower-Middle Cambrian interval and the low-amplitude reflection in the Upper Cambrian-Middle Ordovician interval. The high-amplitude reflection interval thins or wedges out towards the center of the present Southwest Depression section, and thickens to the north and south. Inside of the high-amplitude interval, the seismic reflection terminated at the top reflector. Seismic forward modeling was performed to examine the validity of possible hypothetical models in the studied area. The modeling results show that the simulated stratigraphic patterns are comparable to a ramp or depression geometry which is well fit to the characteristics of actual seismic reflections. Such a ramp or depression geometry is built upon the changes in sea level and climate during the Cambrian period. This study emphasizes the potential of the integration of sequence stratigraphic analyses and seismic forward modeling as a seismic workflow for retrieving the stratigraphic architecture and platform geometry.

Human Umbilical Cord Mesenchymal Stem Cell-Derived Exosomes Loaded Mir-29-3p Targets AhR to Improve Juvenile Idiopathic Arthritis via Inhibiting the Expression of IL-22 in CD4+ T Cell - Xinyi Wei; Kunpeng Sui; Yuanyuan Peng; Sha Li; Yu Fang; Zhi Chen; Xiao Du; Xue Xie; Haiming Tang; QiuYue Wen; JingWei Li; Meilin He; et al. (Stem Cell Reviews and Reports, 2025)

Statistical inference and neural network training based on stochastic difference model for air pollution and associated disease transmission - Sha He; Mengqi He; Sanyi Tang (Journal of Theoretical Biology, 2025)

Effects of polyethylene and poly (butyleneadipate-co-terephthalate) contamination on soil respiration and carbon sequestration - Mengyu Liu; Yao Yu; Ying Liu; Sha Xue; Darrell W.S. Tang; Xiaomei Yang (Environmental Pollution, 2025)

Optimizing energy efficiency in buildings’ cold water systems: A differential pressure control-based global approach - Jinhui Tang; Le Sha; Hejiang Sun; Wenshuai Zhang (Energy and Buildings, 2025)

Effects of LDPE and PBAT plastics on soil organic carbon and carbon-enzymes: A mesocosm experiment under field conditions - Xinkai Jia; Yu Yao; Gaowei Tan; Sha Xue; Mengjuan Liu; Darrell W.S. Tang; Violette Geissen; Xiaomei Yang (Environmental Pollution, 2024)

Unveiling amoxicillin photocatalytic decontamination utilizing CuFe2O4/CuS core-shell heterostructure-integrated peroxymonosulfate activation: Mechanism insights, aquatic hazard assessment, and environmental implementation - Chao Lei; Mingli Ye; Jun Tang; Cun Yu; Sha Yu (Journal of Water Process Engineering, 2024)

A hierarchical residual correction-based hyperspectral inversion method for soil heavy metals considering spatial heterogeneity - Yulong Wang; Bin Zou; Sha Li; Rongcai Tian; Bo Zhang; Huihui Feng; Yuqi Tang (Journal of Hazardous Materials, 2024)

Balancing Maillard reaction products formation and antioxidant activities for improved sensory quality and health benefit properties of pan baked buns - Yao Tang; Yuan Huang; Mengru Li; Wen Zhu; Wei Zhang; Sha Luo; Yingying Zhang; Jie Ma; Yuqian Jiang (Food Research International, 2024)

Switchable transformation of biomass-derived furfural to furfuryl alcohol and isopropyl furfuryl ether over a zirconium-based bifunctional catalyst - Lei Hu; Baogang Sha; Yingxuan Shi; Na Shen; Minhui Yang; Keru Chen; Zhen Wu; Xing Tang; Aiyong He; Lu Lin (Chemical Engineering Journal, 2024)

Long-term vegetation succession enhances the network complexity and stability of soil protozoan communities - Ziwen Zhao; Yang Wu; Wenjing Chen; Guobin Liu; Yakun Tang; Sha Xue (CATENA, 2024)

Heat-moisture treatment of freshly harvested high-amylose maize kernels improves its starch thermal stability and enzymatic resistance - Zhonghua Gu; Gaomin Cheng; Xianying Sha; Haochen Wu; Xinwei Wang; Renyong Zhao; Qiang Huang; Yinong Feng; Jihua Tang; Hongxin Jiang (Carbohydrate Polymers, 2024)

Multi-layer perspective of household-driven carbon emissions reveals new industrial chain hotspots in China - Sha Peng; Kerong Wu; Chang Tang; Bo Meng; Zhen Wang; Hui Li; Sai Liang (Journal of Cleaner Production, 2024)

Adenylate kinase phosphate energy shuttle underlies energetic communication in flagellar axonemes - Huan Wu; Yanman Zhang; Yuqian Li; Shuya Sun; Jintao Zhang; Qingsong Xie; Yue Dong; Shushu Zhou; Xuan Sha; Kuokuo Li; Jinyi Chen; Xin Zhang; et al. (Science China Life Sciences, 2024)

Dynamic variation of dissolved As, Sb, Fe and S in paddy soil triggered by nitrate loading to overlaying water - Zhao-Feng Yuan; Sha Zhang; Williamson Gustave; Tida Ge; Zhenke Zhu; Xiaoyu Shi; Xianjin Tang; Zheng Chen (Journal of Soils and Sediments, 2024)

Effects of uranium mining on the rhizospheric bacterial communities of three local plants on the Qinghai-Tibet Plateau - Yuanmou Tang; Xiaodie Chen; Liming Hou; Jing He; Ajia Sha; Liang Zou; Lianxin Peng; Qiang Li (Environmental Science and Pollution Research, 2024)

Penthorum chinense Pursh leaf tea debittering mechanisms via green tea manufacturing process and its influence on NAFLD-alleviation activities - Xue Tian; Xingyue Wang; Wei Xu; Meng Gong; Chuanyuan Zhou; Ercheng Jiang; Yongqing Tang; Lirong Jia; Li Zeng; Sha Deng; Feixia Duan (Food Chemistry, 2024)

The effect of glycation on the identification of characteristic tryptic peptides from porcine gelatin - Xue-Qi Tang; Guang-Yao Wang; Zi-Zi Hu; Xiao-Mei Sha (Food Hydrocolloids, 2024)

The effect of quorum sensing on cadmium- and lead-containing wastewater treatment using activated sludge: Removal efficiency, enzyme activity, and microbial community - Taotao Zeng; Liangqin Wang; Xiaoya Ren; Naif Abdullah Al-Dhabi; Haichao Sha; Yusong Fu; Wangwang Tang; Jie Zhang (Environmental Research, 2024)

Tannic acid mediated hollow biocatalytic zeolitic imidazolate frameworks as a “three-in-one” label for enhancing the sensitivity of fluorescence immunosensor - Xudong Jing; Xinliu Tan; Zhou Yu; Yanyan Tang; Sha Yu; Gan Zhang; Yonghua Xiong; Daofeng Liu; Weihua Lai (Chemical Engineering Journal, 2024)

Metagenomic Next-Generation Sequencing Contributes to the Early Diagnosis of Mixed Infections in Central Nervous System - Li Lin; Junyue Fang; Jiahao Li; Ying Tang; Tengteng Xin; Nengtai Ouyang; Wenying Cai; Lisi Xie; Sha Lu; Junmin Zhang (Mycopathologia, 2024)

Temporal-spatial characteristics and sources of heavy metals in bulk deposition across China - Xin Ma; Zhipeng Sha; Yunzhe Li; Ruotong Si; Aohan Tang; Andreas Fangmeier; Xuejun Liu (Science of The Total Environment, 2024)

Self-assembly and aggregation behavior of temperature-controlled modified glycinin and d-galactose colloidal particles - Shiqi Tang; Panling Liu; Sha Zhu; Tianzhan Kou; Yang Li; Lianzhou Jiang; Baokun Qi (Food Chemistry, 2024)

Comprehensive assessment of the microbial community structure in a typical lead–zinc mine soil - Taotao Zeng; Haichao Sha; Qingqing Xie; Yue Lu; Haidu Nong; Liangqin Wang; Lin Tang (Environmental Science and Pollution Research, 2024)

Growth differentiation factor 9 regulates the expression of estrogen receptors via Smad2/3 signaling in goat cumulus cells - Yaju Tang; Sihai Lu; Juncai Wei; Rui Xu; Hui Zhang; Qiang Wei; Bin Han; Yan Gao; Xiaoe Zhao; Sha Peng; Menghao Pan; Baohua Ma (Theriogenology, 2024)

Genetic diversity of grain yield traits and identification of a grain weight gene SiTGW6 in foxtail millet - Hui Zhang; Sha Tang; Honglu Wang; Yannan Wang; Hui Zhi; Bin Liu; Renliang Zhang; Qian Ma; Guanqing Jia; Baili Feng; Xianmin Diao (Theoretical and Applied Genetics, 2024)

Mn-CaCO3-based nanosystem for augmented sonodynamic-chemodynamic immunotherapy via PI3K/Akt signaling pathway - Mashiti Sha; Huansong Li; Yangsui Liu; Cong Tang; Xue Bai; Yun Wang; Bo Yuan; Kairui Liu; Xiaoning Gao; Jun Yan; Silong Wei; Jin Chang; et al. (Chemical Engineering Journal, 2024)

Peroxymonosulfate activation by trace iron(III) porphyrin for facile degradation of organic pollutants via nonradical oxidation - Lu Liu; Jingping Hu; Jianjian Tang; Sijing Chen; Longsheng Wu; Zhen Li; Huijie Hou; Sha Liang; Jiakuan Yang (Chemosphere, 2024)

A complete reference genome assembly for foxtail millet and Setaria-db, a comprehensive database for Setaria - Qiang He; Chunchao Wang; Qiang He; Jun Zhang; Hongkai Liang; Zefu Lu; Kun Xie; Sha Tang; Yuhan Zhou; Bin Liu; Hui Zhi; Guanqing Jia; et al. (Molecular Plant, 2024)

China’s cross-regional carbon emission spillover effects of urbanization and industrial shifting - Xiao Zhang; Xiao Wang; Chang Tang; Tongtong Lv; Sha Peng; Zhen Wang; Bo Meng (Journal of Cleaner Production, 2024)

Insights into the rapid start-up of an inoculated municipal sludge system: A high-height-to-diameter-ratio airlift inner-circulation partition bioreactor based on CFD analysis - Hong Chen; Chengfeng Zhang; Naif Abdullah Al-Dhabi; Sha Wu; Yangkai Liu; Lvzhou Wu; Zhe Kong; Wangwang Tang; Jing Chen; Lixiu Shi; Guina Luo (Environmental Research, 2024)

3D network of zinc powder woven into fibre filaments for dendrite-free zinc battery anodes - Lin Sha; Bin-Bin Sui; Peng-Fei Wang; Zhe Gong; Yu-Hang Zhang; Yu-Han Wu; Li-Na Zhao; Jun-Jie Tang; Fa-Nian Shi (Chemical Engineering Journal, 2024)

Effects of biochar layer position on treatment performance and microbial community in subsurface flow constructed wetlands for removal of cadmium and lead - Haichao Sha; Xin Song; Naif Abdullah Al-Dhabi; Taotao Zeng; Yuemei Mao; Yusong Fu; Zheng Liu; Guohua Wang; Wangwang Tang (Bioresource Technology, 2024)

Climate-shaped vegetation dominated the spatial pattern of the Bowen ratio over terrestrial ecosystems in China - Mingyu Sun; Guirui Yu; Zhi Chen; Tianxiang Hao; Meng Yang; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Yuan Yao; et al. (Agricultural and Forest Meteorology, 2024)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Short-chain fatty acids facilitated long-term dechlorination of PCBs in Taihu Lake sediment microcosms: Evidence from PCB congener and microbial community analyses - Lei Xu; Yanqiang Tang; Sha Liu; Xi Chen; Ying Wang; Zheming Liu; Qingdong Qin; Dafang Fu; Yan Xu (Chemosphere, 2023)

Developing a model-ready highly resolved HONO emission inventory in Guangdong using domestic measured emission factors - Xiaohong Yin; Feng Tang; Zhijiong Huang; Songdi Liao; Qinge Sha; Peng Cheng; Menghua Lu; Zhen Li; Fei Yu; Yuanqian Xu; Min Shao; Junyu Zheng (Science of The Total Environment, 2023)

A tumor microenvironment responsive titanium-based nanosonosensitizer for combination sonodynamic-immunotherapy with calcium ion overload - Cong Tang; Huansong Li; Mashiti Sha; Jianyin Song; Xue Bai; Kairui Liu; Yangsui Liu; Bo Yuan; Jun Yan; Jin Chang; Jun Kang (Chemical Engineering Journal, 2023)

Physicochemical effect on soil in sliding zone of reservoir landslides - Xuexue Su; Wei Wu; Huiming Tang; Lei Huang; Ding Xia; Sha Lu (Engineering Geology, 2023)

Primary cutaneous cryptococcosis presenting as ulcers in solid organ transplant recipient - Ying Tang; Wenying Cai; Li Lin; Jiahao Li; Hsingmei Liu; Liyan Xi; Sha Lu (Mycopathologia, 2023)

Epidemiology and Clinical Findings of Tinea Capitis: A 23-Year Retrospective, Single-Center Study in Guangzhou, China - Wenying Cai; Junhao Huang; Jiahao Li; Li Lin; Liyan Xi; Junmin Zhang; Xiqing Li; Zhen Zhou; Ying Tang; Hsingmei Liu; Jing Zhang; Sha Lu (Mycopathologia, 2023)

Randomness accelerates the dynamic clearing process of the COVID-19 outbreaks in China - Sha He; Dingding Yan; Hongying Shu; Sanyi Tang; Xia Wang; Robert A. Cheke (Mathematical Biosciences, 2023)

CRISPR/Cas9-mediated BoaAOP2s editing alters aliphatic glucosinolate side-chain metabolic flux and increases the glucoraphanin content in Chinese kale - Hao Zheng; Wenli Huang; Xiangxiang Li; Huanhuan Huang; Qiao Yuan; Ruobin Liu; Hongmei Di; Sha Liang; Mengyu Wang; Mengyao Li; Zhi Huang; Yi Tang; et al. (Food Research International, 2023)

Solvent-free quasi-solid polymer electrolyte with a high dielectric constant for stable lithium metal anodes - Xuechun Lou; Jun Zhong; Danpeng Cheng; Qigao Han; Fuhe Wang; Shuaijing Ji; Wuxin Sha; Fengqian Wang; Jie Tian; Weixin Zhang; Shun Tang; Yuan-Cheng Cao; et al. (Chemical Engineering Journal, 2023)

Surface-enhanced Raman spectroscopy charged probes under inverted superhydrophobic platform for detection of agricultural chemicals residues in rice combined with lightweight deep learning network - Shizhuang Weng; Le Tang; Mengqing Qiu; Jinghong Wang; Yehang Wu; Rui Zhu; Cong Wang; Pan Li; Wen Sha; Dong Liang (Analytica Chimica Acta, 2023)

Rational design of molecular phototheranostic platform for NIR-II fluorescence imaging guided chemodynamic-photothermal combined therapy - Gui-long Wu; Bin Sun; Yuxuan He; Xiaofeng Tan; Qi Pan; Sha Yang; Na Li; Minghui Wang; Peixian Wu; Fen Liu; Hao Xiao; Li Tang; et al. (Chemical Engineering Journal, 2023)

Ecological restoration exacerbates the agriculture-induced water crisis in North China Region - Yan Zhou; Jinwei Dong; Yaoping Cui; Meng Zhao; Xinxin Wang; Qiuhong Tang; Yongqiang Zhang; Sha Zhou; Graciela Metternicht; Zhenhua Zou; Geli Zhang; Xiangming Xiao (Agricultural and Forest Meteorology, 2023)

The detection of major clades and new species of Mallocybe (Inocybaceae, Agaricales) from China with elongate cheilocystidia - Jian-Hua Hu; Wen-Jie Yu; Lun-Sha Deng; Yu-Guang Fan; Tolgor Bau; Li-Ping Tang; Wen-Fei Lin; Chun-Ying Deng (Mycological Progress, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Evolution of household carbon emissions and their drivers from both income and consumption perspectives in China during 2010–2017 - Sha Peng; Xiao Wang; Qian Du; Kerong Wu; Tongtong Lv; Zheng Tang; Liyuan Wei; Jinjun Xue; Zhen Wang (Journal of Environmental Management, 2023)

Identification and haplotype analysis of SiCHLI: a gene for yellow–green seedling as morphological marker to accelerate foxtail millet (Setaria italica) hybrid breeding - Hongkai Liang; Qiang He; Hui Zhang; Hui Zhi; Sha Tang; Hailong Wang; Qiang Meng; Guanqing Jia; Jinhua Chang; Xianmin Diao (Theoretical and Applied Genetics, 2023)

Effect of empirical antifungal treatment on mortality in non-neutropenic critically ill patients: a propensity-matched retrospective cohort study - Yue Tang; Wenjing Hu; Shuangyan Jiang; Maoyu Xie; Wenying Zhu; Lin Zhang; Jing Sha; Tengfei Wang; Min Ding; Juan Zeng; Jinjiao Jiang (European Journal of Clinical Microbiology & Infectious Diseases, 2022)

A two-year (2020–2021) observation of marine phycotoxins in phytoplankton in typical mariculture areas of East China Sea - Xiaoqing Tian; Chengqi Fan; Yunyu Tang; Haiyan Zhang; Wei Kang; Sha Chen; Chongbin Li; Ya’nan Lu (Journal of Oceanology and Limnology, 2022)

Assessment of the Bioavailability of Mercury Sulfides in Paddy Soils Using Sodium Thiosulfate Extraction - Results from Microcosm Experiments - Hong Li; Yunyun Li; Wenli Tang; Huan Zhong; Jiating Zhao; Xu Bai; Shengnan Sha; Diandou Xu; Pei Lei; Yuxi Gao (Bulletin of Environmental Contamination and Toxicology, 2022)

Spatial and seasonal variation and sources of deposition fluxes of polycyclic aromatic hydrocarbons (PAHs) in Shanghai - Jian Wu; Chenyan Sha; Dayan Li; Cheng Shen; Hao Tang; Shenfa Huang (Environmental Science and Pollution Research, 2022)

Biogeographic role of the Indonesian Seaway implicated by colonization history of purpleback flying squid, Sthenoteuthis oualaniensis (Lesson, 1830), in the Indo-Pacific Ocean - Lijun He; Shasha Xu; David A. Weese; Jie Zhang; Huimin Ren; Fenghua Tang; Zhongli Sha; Jing Zhang (Frontiers in Marine Science, 2022)
As a bio]diversity hotspot, the East Indies (Coral) Triangle possesses the highest biodiversity on the earth. However, evolutionary hypotheses around this area remain controversial; e.g., center of origin, center of accumulation, and center of overlap have been supported by different species. This study aims to answer the evolutionary influence of the Indonesian Seaway on the biodiversity of the Coral Triangle by recovering the evolutionary origins of a wide-ranging ommastrephid squid ( Sthenoteuthis oualaniensis ) based on integrated molecular and oceanographic clues from the Indo-Pacific. Three new clades were revealed; viz., clade I from the South China Sea, clade II from the northern East Indian Ocean, and clade III from the southern East Indian Ocean. These two Indian Ocean clades formed a monophyly closely related to clade IV from the Central-Southeast Pacific. Clade VI from the central Equatorial Pacific and clade V from the northern Eastern Pacific sit in basal positions of phylogenetic trees. Ancestral Sthenoteuthis was inferred to have originated from the Atlantic Ocean and sequentially dispersed to the northern East Pacific, central Equatorial Pacific, and West Pacific through the open Panama Seaway and being transported by westward North Equatorial Current. The East Indian Ocean was likely colonized by an ancestral population of clade IV from the Southeast Pacific. Westward South Equatorial Circulation could have promoted transoceanic migration of S. oualaniensis through the wide paleo-Indonesian Seaway. Sea level regression since the Miocene and the closure of the Indonesian Seaway at 4–3 Ma were responsible for the population genetic differentiation of S. oualaniensis in the Indo-Pacific. Therefore, the Indonesian Gateway played an important role in influencing marine organisms’ migration and population differentiation through controlling and reorganizing circulations in the Indo-Pacific.

ML323, a USP1 inhibitor triggers cell cycle arrest, apoptosis and autophagy in esophageal squamous cell carcinoma cells - Yaxin Sun; Beibei Sha; Wenjing Huang; Miaomiao Li; Shan Zhao; Yuan Zhang; Jie Yan; Zheng Li; Jingwen Tang; Peiyan Duan; Jianxiang Shi; Pei Li; et al. (Apoptosis, 2022)

Can the Leading Officials’ Accountability Audit of Natural Resources policy stimulate Chinese heavy-polluting enterprises’ green behavior? - Yunqiang Liu; Yanan She; Sha Liu; Hong Tang (Environmental Science and Pollution Research, 2022)

Identification of the Largest SCA36 Pedigree in Asia: with Multimodel Neuroimaging Evaluation for the First Time - Yue Xie; Zhao Chen; Zhe Long; Rui-Ting Chen; Yi-Zheng Jiang; Ming-Jie Liu; Lin-Liu Peng; Hui-Rong Peng; Na Wan; Guangdong Zou; Chun-Rong Wang; Yu-Ting Shi; et al. (The Cerebellum, 2022)

Activating PIK3CA postzygotic mutations in segmental overgrowth of muscles with bone involvement in the body extremities - Wen Tian; Liying Sun; Qi Zhang; Junhui Zhao; Yang Guo; Wenyao Zhong; Liu Liu; Katia Meirelles; Sha Tang; Jing Zhang; Yingzhao Huang; Yuehan Yin; et al. (Molecular Genetics and Genomics, 2022)

Impact of caterpillars and plant-parasitic nematodes on Chinese tallow tree are more strongly affected by nematode density than by caterpillar identity - Sha Yang; Wenfeng Guo; Jun Tang; Wei Wang; Qingbiao Wu; Xiaoqiong Li (Arthropod-Plant Interactions, 2022)

The Phenotypes and Mechanisms of NOTCH2NLC-Related GGC Repeat Expansion Disorders: a Comprehensive Review - Xiu-Rong Huang; Bei-Sha Tang; Peng Jin; Ji-Feng Guo (Molecular Neurobiology, 2022)

Hydrogen Sulfide Maintains Good Nutrition and Delays Postharvest Senescence in Postharvest Tomato Fruits by Regulating Antioxidative Metabolism - Ting-Ying Zhong; Gai-Fang Yao; Sha-Sha Wang; Ting-Ting Li; Ke-Ke Sun; Jun Tang; Zhong-Qin Huang; Feng Yang; Yan-Hong Li; Xiao-Yan Chen; Lan-Ying Hu; Hua Zhang; et al. (Journal of Plant Growth Regulation, 2021)

Carbonic Anhydrase III Attenuates Hypoxia-Induced Apoptosis and Activates PI3K/Akt/mTOR Pathway in H9c2 Cardiomyocyte Cell Line - Hua Li; Yibin Liu; Sha Tang; Jie Hu; Qiuling Wu; Yang Wei; Ming Niu (Cardiovascular Toxicology, 2021)

Qaidamihabitans albus gen. nov., sp. nov., a new member of the family Pseudonocardiaceae, and transfer of Prauserella shujinwangii to Qaidamihabitans gen. nov. as Qaidamihabitans shujinwangii comb. nov. - Li-Sha Tian; Gang-Qiang Jiang; Rui Li; Ping Ni; Chuan-En Li; Hong-Yan Zhang; Juan Wang; Xiao-Ping Zhang; Yun Wang; Shu-Kun Tang (Archives of Microbiology, 2021)

Sedimentary Environmental Evolution of the Western Taiwan Shoal Area since the Late Pleistocene - Chipeng He; Longbin Sha; Dongbo Zhao; Lu Dai; Zheng Li; Jiabing Tang; Xianfu Li; Dongling Li (Journal of Marine Science and Engineering, 2021)
A new pollen analysis and major and trace element contents were conducted on a 40 m long gravity core recovered from the Taiwan Shoal (sand ridges), south of the Taiwan Strait, beginning in the Late Pleistocene. The changes in the pollen assemblage and concentration represent the climate change around the Taiwan Shoal and the strength of the Zhe-Min Coastal Current, whereas variations in major and trace element contents can imply the source of the sediments in the Taiwan Shoal, which are correlated with the rise or fall of the sea level with increased marine dinoflagellate cysts. The interval of 40–30 m was characterized by high pollen and spore concentrations, and evergreen Quercus was dominant taxon, which indicates a warm sedimentary environment, and the surrounding area of the Taiwan Shoal were covered by a tropical and subtropical broad-leaved forest. There were no pollen and spores from 30–24 m, which indicates a strong hydrodynamic sedimentary environment, and most of the Taiwan Shoal might have been experience subaerial exposure. The interval of 24–17 m was characterized by the reappearance of pollen and spores, as well as marine dinoflagellate cysts and foraminifera, suggesting the climate was warm and wet in the study area and an apparent marine sedimentary environment with relatively high sea level. Deciduous Quercus dominated the interval of 17–12 m, which indicated that the climate was relatively cool, corresponding to the end of Marine isotope stages3 (MIS3) to the Last Glacial Maximum accompanied by weathering and denudation. Above 12 m, the low pollen concentration with increased marine dinoflagellate cysts and foraminifera abundance suggested a marine sedimentary environment in the Taiwan Shoal. The high concentrations in Pinus corresponds to Holocene high sea level.

Genetic control and phenotypic characterization of panicle architecture and grain yield-related traits in foxtail millet (Setaria italica) - Hui Zhi; Qiang He; Sha Tang; Junjun Yang; Wei Zhang; Huifang Liu; Yanchao Jia; Guanqing Jia; Aiying Zhang; Yuhui Li; Erhu Guo; Ming Gao; et al. (Theoretical and Applied Genetics, 2021)

SiMADS34, an E-class MADS-box transcription factor, regulates inflorescence architecture and grain yield in Setaria italica - Shareif Hammad Hussin; Hailong Wang; Sha Tang; Hui Zhi; Chanjuan Tang; Wei Zhang; Guanqing Jia; Xianmin Diao (Plant Molecular Biology, 2021)

QTL mapping for foxtail millet plant height in multi-environment using an ultra-high density bin map - Qiang He; Hui Zhi; Sha Tang; Lu Xing; Suying Wang; Haigang Wang; Aiying Zhang; Yuhui Li; Ming Gao; Haijin Zhang; Guoqiu Chen; Shutao Dai; et al. (Theoretical and Applied Genetics, 2021)

A stochastic epidemic model coupled with seasonal air pollution: analysis and data fitting - Sha He; Sanyi Tang; Yongli Cai; Weiming Wang; Libin Rong (Stochastic Environmental Research and Risk Assessment, 2020)

Aberrant cerebellar neural activity and cerebro-cerebellar functional connectivity involving executive dysfunction in schizophrenia with primary negative symptoms - Ju Gao; Xiaowei Tang; Congjie Wang; Miao Yu; Weiwei Sha; Xiang Wang; Hongying Zhang; Xiangrong Zhang; Xiaobin Zhang (Brain Imaging and Behavior, 2020)

De novo transcriptome sequencing and identification of genes related to salt and PEG stress in Tetraena mongolica Maxim - Ningmei Chen; Jinchao Feng; Buerbatu Song; Shuai Tang; Junqing He; Yijun Zhou; Sha Shi; Xiaojing Xu (Trees, 2019)

Katian oncoids of the lower Ordovician Lianglitage Formation in the Tarim Basin, Northwest China - Shi Pingzhou; Tang Hongming; Wang Zhengyu; Sha Xuguang (Carbonates and Evaporites, 2019)

Microscopic characterization of microcrack development in marble after cyclic treatment with high temperature - Jun Peng; Guan Rong; Zhicheng Tang; Song Sha (Bulletin of Engineering Geology and the Environment, 2019)

Leaf Senescence can be Induced by Inhibition of Root Respiration - Gang-liang Tang; Xiang-yi Li; Li-sha Lin; Zhu-yu Gu; Fan-jiang Zeng (Journal of Plant Growth Regulation, 2019)

Spatial Distribution and Potential Sources of Five Heavy Metals and One Metalloid in the Soils of Xiamen City, China - Sha Huang; Guofan Shao; Luyan Wang; Lina Tang (Bulletin of Environmental Contamination and Toxicology, 2019)

AdipoRon, an adiponectin receptor agonist, attenuates cardiac remodeling induced by pressure overload - Ning Zhang; Wen-Ying Wei; Hai-Han Liao; Zheng Yang; Can Hu; Sha-sha Wang; Wei Deng; Qi-Zhu Tang (Journal of Molecular Medicine, 2018)

Overexpression of the ABC transporter gene TsABCG11 increases cuticle lipids and abiotic stress tolerance in Arabidopsis - Ningmei Chen; Buerbatu Song; Shuai Tang; Junqing He; Yijun Zhou; Jinchao Feng; Sha Shi; Xiaojing Xu (Plant Biotechnology Reports, 2018)

Effects of the particle-size distribution on the micro and macro behavior of soils: fractal dimension as an indicator of the spatial variability of a slip zone in a landslide - Sha Lu; Huiming Tang; Yongquan Zhang; Wenping Gong; Liangqing Wang (Bulletin of Engineering Geology and the Environment, 2018)

An optical material for the detection of trace S2O3 2− in milk based on a copper complex - Qingming Wang; Huifang Sun; Weilin Sha; Juan Chen; Liuyue Gu; Dong Wang; Xinhui Tang (BioMetals, 2017)

Pilot-Scale Study on Treating Wastewater from Magnesium-Based Exhaust Gas Cleaning System by a Novel Process - Tie Li; Lin Sha; Quan Liu; Jiao Zhao; Xiaojia Tang; Yimin Zhu (Water, Air, & Soil Pollution, 2017)

The Chlorophyll a Fluorescence Characteristic in Different Types of Leaf Senescence in Alhagi sparsifolia - Gang-Liang Tang; Xiang-Yi Li; Li-Sha Lin; Zhu-Yu Gu; Fan-Jiang Zeng (Journal of Plant Growth Regulation, 2016)

Molecular cytogenetic characterization of a new wheat-rye 1BL•1RS translocation line expressing superior stripe rust resistance and enhanced grain yield - Weiliang Qi; Yao Tang; Wei Zhu; Daiyan Li; Chengdou Diao; Lili Xu; Jian Zeng; Yi Wang; Xing Fan; Lina Sha; Haiqin Zhang; Youliang Zheng; et al. (Planta, 2016)

Different causes of photosynthetic decline and water status in different stages of girdling in Alhagi sparsifolia Shap. (Fabaceae) - Gang-liang Tang; Xiang-yi Li; Li-sha Lin; Fan-jiang Zeng (Brazilian Journal of Botany, 2016)

Identifying patellin-like genes in Glycine max and elucidating their response to phosphorus starvation - Aihua Sha; Yanni Qi; Zhihui Shan; Haifeng Chen; Zhonglu Yang; Dezheng Qiu; Xinan Zhou; Yinhua Chen; Jinshan Tang (Acta Physiologiae Plantarum, 2016)

Impact of phloem girdling on water status in desert plants Alhagi sparsifolia Shap. (Fabaceae) and Karelinia Caspica (Pall.) Less. (Asteraceae) - Gang-liang Tang; Xiang-yi Li; Li-sha Lin; Zi-chun Guo; Chang-jun Li; Hui Guo; Fan-jiang Zeng (Brazilian Journal of Botany, 2015)

Analysis of the Drought Stress-Responsive Transcriptome of Black Cottonwood (Populus trichocarpa) Using Deep RNA Sequencing - Sha Tang; Yan Dong; Dan Liang; Zhoujia Zhang; Chu-Yu Ye; Peng Shuai; Xiao Han; Ying Zhao; Weilun Yin; Xinli Xia (Plant Molecular Biology Reporter, 2015)

Erratum to: Poplar GATA transcription factor PdGNC is capable of regulating chloroplast ultrastructure, photosynthesis, and vegetative growth in Arabidopsis under varying nitrogen levels - Yi An; Xiao Han; Sha Tang; Xinli Xia; Weilun Yin (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

Poplar GATA transcription factor PdGNC is capable of regulating chloroplast ultrastructure, photosynthesis, and vegetative growth in Arabidopsis under varying nitrogen levels - Yi An; Xiao Han; Sha Tang; Xinli Xia; Weilun Yin (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

Response of artificial grassland carbon stock to management in mountain region of Southern Ningxia, China - Long Tang; Xiaohu Dang; Guobin Liu; Chuanke Shao; Sha Xue (Chinese Geographical Science, 2014)

Expanding the clinical and mutational spectrum of Kaufman oculocerebrofacial syndrome with biallelic UBE3B mutations - Lina Basel-Vanagaite; Rüstem Yilmaz; Sha Tang; Miriam S. Reuter; Nils Rahner; Dorothy K. Grange; Megan Mortenson; Patrick Koty; Heather Feenstra; Kelly D. Farwell Gonzalez; Heinrich Sticht; Nathalie Boddaert; et al. (Human Genetics, 2014)

The Dynamic Evaluation of Rock Slope Stability Considering the Effects of Microseismic Damage - N. W. Xu; F. Dai; Z. Z. Liang; Z. Zhou; C. Sha; C. A. Tang (Rock Mechanics and Rock Engineering, 2014)

Lithium Chloride Alleviates Neurodegeneration Partly by Inhibiting Activity of GSK3β in a SCA3 Drosophila Model - Dan-Dan Jia; Li Zhang; Zhao Chen; Chun-Rong Wang; Feng-Zhen Huang; Ran-Hui Duan; Kun Xia; Bei-Sha Tang; Hong Jiang (The Cerebellum, 2013)

Populus euphratica: the transcriptomic response to drought stress - Sha Tang; Haiying Liang; Donghui Yan; Ying Zhao; Xiao Han; John E. Carlson; Xinli Xia; Weilun Yin (Plant Molecular Biology, 2013)

Clinical Benefit of Delamanid (OPC-67683) in the Treatment of Multidrug-Resistant Tuberculosis Patients in China - Qing Zhang; Yidian Liu; Shenjie Tang; Wei Sha; Heping Xiao (Cell Biochemistry and Biophysics, 2013)

Microbiota Regulates the TLR7 Signaling Pathway Against Respiratory Tract Influenza A Virus Infection - Sha Wu; Zhen-You Jiang; Yi-Fan Sun; Bin Yu; Jia Chen; Cong-Qi Dai; Xian-Lin Wu; Xiao-Long Tang; Xiao-Yin Chen (Current Microbiology, 2013)

Microparameter Prediction for a Triaxial Compression PFC3D Model of Rock Using Full Factorial Designs and Artificial Neural Networks - Miao-jun Sun; Hui-ming Tang; Xin-li Hu; Yun-feng Ge; Sha Lu (Geotechnical and Geological Engineering, 2013)

An EST dataset for Metasequoia glyptostroboides buds: the first EST resource for molecular genomics studies in Metasequoia - Ying Zhao; Shivegowda Thammannagowda; Margaret Staton; Sha Tang; Xinli Xia; Weilun Yin; Haiying Liang (Planta, 2013)

Effect of tonsillar mononuclear cell supernatants in patients with IgA nephropathy on renal tubular epithelial cells - Youzhou Tang; Youming Peng; Sha Yang; Hong Liu; Gang Wu; Fuyou Liu (Inflammation Research, 2013)

Expression of Th17 Cells in Breast Cancer Tissue and Its Association with Clinical Parameters - LiJuan Yang; YiXin Qi; Jie Hu; Longmei Tang; Sha Zhao; BaoEn Shan (Cell Biochemistry and Biophysics, 2012)

Molecular cloning, characterization and expression of cDNA encoding translationally controlled tumor protein (TCTP) from Jatropha curcas L - Xiaobo Qin; Fan Gao; Jinping Zhang; Jihai Gao; Sha Lin; Yong Wang; Luding Jiang; Yi Liao; Lina Wang; Yongjiong Jia; Lin Tang; Ying Xu; et al. (Molecular Biology Reports, 2011)

Rampant gene rearrangement and haplotype hypervariation among nematode mitochondrial genomes - Bradley C. Hyman; Samantha C. Lewis; Sha Tang; Zhen Wu (Genetica, 2011)

Association of the DRD2 and DRD3 polymorphisms with response to pramipexole in Parkinson’s disease patients - Ying-Zi Liu; Bei-Sha Tang; Xin-Xiang Yan; Jie Liu; Dong-Sheng Ouyang; Li-Nuo Nie; Lan Fan; Zhi Li; Wei Ji; Dong-Li Hu; Dan Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2009)

Lack of variation of ATTCT pentanucleotide repeats at ATXN10 gene between clinically diagnosed ataxia patients and normal individuals originated from Chinese Han - Jun-Ling Wang; Hong Jiang; Shen Zhang; Qian Xu; Ya-Fang Zhou; Shu-Sheng Liao; Lu Shen; Xin-Xiang Yan; Huai-Xu Zhu; Qian Pan; Kun Xia; Bei-Sha Tang (Journal of Genetics, 2008)

Allomermis solenopsi n. sp. (Nematoda: Mermithidae) parasitising the fire ant Solenopsi s invicta Buren (Hymenoptera: Formicidae) in Argentina - George O. Poinar; Sanford D. Porter; Sha Tang; Bradley C. Hyman (Systematic Parasitology, 2007)

Pluripotency and Chimera Competence of an Embryonic Stem Cell Line from the Sea Perch (Lateolabrax japonicus) - Song-Lin Chen; Zhen-Xia Sha; Han-Qing Ye; Yang Liu; Yong-Sheng Tian; Yunhan Hong; Qi-Sheng Tang (Marine Biotechnology, 2007)

Small heat-shock protein 22 mutated in autosomal dominant Charcot-Marie-Tooth disease type 2L - Bei-sha Tang; Guo-hua Zhao; Wei Luo; Kun Xia; Fang Cai; Qian Pan; Ru-xu Zhang; Fu-feng Zhang; Xiao-min Liu; Biao Chen; Cheng Zhang; Lu Shen; et al. (Human Genetics, 2005)

A new locus for autosomal dominant Charcot-Marie-Tooth disease type2 (CMT2L) maps to chromosome 12q24 - Lu Shen; Jian-guang Tang; Guo-hua Zhao; Qian Pan; He-ping Dai; Oleg V. Evgrafov; Wei Luo; Kun Xia; Fang Cai; Qi-dong Yang; Jia-hui Xia; Bei-sha Tang; et al. (Human Genetics, 2004)

Mycorrhiza of plants in different vegetation types in tropical ecosystems of Xishuangbanna, southwest China - T. Muthukumar; Liqing Sha; Xiaodong Yang; Min Cao; Jianwei Tang; Zheng Zheng (Mycorrhiza, 2003)